DLX4 regulates rheumatoid arthritis fibroblast-like synoviocytes invasiveness and a cancer transcriptomic signature - Teresina Laragione; Carolyn Harris; Percio S. Gulko (Scientific Reports)
Abstract The fibroblast-like synoviocyte (FLS) has a central role in rheumatoid arthritis (RA) pathogenesis and its invasive behavior strongly correlates with disease severity and joint damage. Yet, the regulation of FLS invasiveness is incompletely understood. Distal-less homeobox 4 (DLX4) is a transcription factor implicated in cancer cell invasion and metastasis, and we considered that it might also be involved in the regulation of FLS phenotypes. siRNA was used to knockdown DLX4 in RA FLS, compared with a control siRNA. Cells were then studied in invasion, migration, proliferation and adhesion assays, and RNA was used for RNA sequencing and pathway analyses. siRNA knockdown of DLX4 significantly reduced RA FLS invasiveness (P = 0.028) and migration in the scratch/wound healing assay (P = 0.008). RNA sequencing analyses revealed that DLX4 knockdown significantly affected processes and pathways implicated genes involved in diverse types of cancer and in cancer biology, including cell invasion, cell cycle, DNA replication, transcription, p53 signal transduction, RHO GTPase signaling, regulation of cytokinesis, as well as response to oxygen levels and to oxidative stress. HMOX1 and SOD2 were among the genes with the most significantly increased expression, while CPNE3 and HADHA were among those with the most significantly decreased expression in FLS knocked down for DLX4 compared with controls. We describe a new role for DLX4 in the regulation of RA FLS behaviors relevant to disease pathogenesis and joint damage, and identify a new transcriptomic signature regulated by this gene. These findings raise the possibility that DLX4, or one of its target genes and pathways may become a target for treatment.